Effects of a Novelty Virtual Interactive Brain Atlas on Student Perception of Neuroanatomy - Davies H.C; Edwards D.N; George J; Xie R; Kadish I (International Journal of Human Anatomy, 2024)
The instructional techniques in neuroanatomy laboratories continue to evolve to incorporate online interactive resources to improve student experience and outcomes. This study aims to design an “all in one”Virtual Interactive Brain Atlas (VIBA) that provides students with an educational resource that will improve their knowledge of neuroanatomy while in the brain lab and provide them with lab resources they can self-study and self-test. Coronal, midsagittal, whole brain, and horizontal brain slices were used to create detailed descriptions, interactive features, and quiz assessments to create VIBA. Upper level undergraduate and optometry students taking a neuroanatomy one-semester course were provided with VIBA for use during the semester. A paper survey was distributed after completing the course to determine student perception. No significant difference was indicated between the student groups regarding their self-reported understanding prior to the brain lab (p= 0.194) and after the brain lab (p= 0.308). There was a significant difference between the student populations when stating that they strongly agreed that the online brain atlas improved their understanding of neuroanatomy (p= 0.032) and that the VIBA tool was easy to navigate (p=0.048). There was a significant difference between the two student groups that strongly agreed that the online brain atlas quality was sufficient (p= 0.015). This online interactive brain atlas was created in a time-efficient manner from readily available models and was well received by experienced neuroanatomy faculty and students.
Keywords: Brain Atlas